Peran Kepercayaan Konsumen dalam Memediasi Pengaruh Customer Satisfaction dan Citra Merek terhadap Minat Pembelian Ulang: (Studi pada Konsumen Indomaret Kembang Larangan di Tangerang) - Khofifa Dwi Lestari; Yugi Setyarko (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This research aims to examine the role of consumer trust in mediating the influence of customer satisfaction and brand image on repurchase intention among Indomaret Kembarang Larang consumers in Tangerang. The method used is descriptive quantitative using a questionnaire. The analysis technique used in this research is Path Analysis. Sampling in this study used a purposive sampling technique with a sample size of 99 consumers. Data was collected through a questionnaire with an interval scale which was processed using Microsoft Excel 2013 and SmartPLS version 4.1.0.2 software. The results of this research indicate that the customer satisfaction variable has a positive and significant effect on repurchase intention. The brand image variable does not have a significant effect on repurchase intention. The consumer trust variable has a positive and significant effect. The customer satisfaction variable has a positive and significant effect on consumer trust. The brand image variable has a positive and significant effect on consumer trust. The consumer trust variable is able to mediate the customer satisfaction and brand image variables on repurchase intention.